Familiarity and conviction in the criminal justice system: definitions, theory, and eyewitness research - Pozzulo, Joanna (American Psychology-Law Society series, 2020)
1. Defining familiarity and overview of concepts -- 2. Theoretical underpinnings: A Social psychological perspective -- 3. Theoretical underpinnings: A Cognitive psychological perspective -- 4. Eyewitness descriptions and identifications of familiar perpetrators -- 5. Factors that can interact with familiarity: System variables -- 6. Factors that can interact with familiarity: Estimator variables -- 7. Considering familiarity as a dependent variable -- 8. How persuasive is an eyewitness who is familiar with the defendant? -- 9. Future directions for research examining the notion of familiarity and its impact on the criminal justice system.